Faktor-faktor yang Menentukan Keputusan Konsumen dalam Pembelian dan Konsumsi Smoothie Bowl di Restoran Nalu Bowls Seminyak - RUTH MADEARNI MALAU; I WAYAN WINDIA; I DEWA GEDE AGUNG (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Factors that Determine Consumer Decisions in Buying and Consuming SmoothieBowls at Nalu Bowls Restaurant in Seminyak Trade competition, especially in the culinary/food sector, is very strict, requiring allbusiness owners, espesially restaurant business, to be more courageous in takinginnovations. The purpose of these innovations is sales, and can influence the decision ofconsumers to buy a product. Restaurant Nalu Bowls is a business venture that isengaged in the culinary field and is one of the restaurant innovations that has its ownpicture to meet consumer needs, namely a healthy food menu that it offers. In the mostfamous Nalu Bowls, research in needed.The purpose of this study were (1) to analyzethe characteristics of consumers in Nalu Bowl Restaurant, (2) Analyze the decisionprocess in the purchase of a smoothie bowl at Nalu Bowls Restaurant, (3) Analyze thefactors that influence consumer decisions to buy products in Nalu Bowls Restaurant.Theresults of the study show that several stages of the restaurant of Nalu Bowls Restaurantconsumers before making a purchase, namely needs recognition, information search,alternative evaluation, purchase and post-purchase. Factors affecting consumers indeciding the purchase of smoothie bowls consist of three factors, namely product andsupporting factors, service factors and restaurant identity, and food appearance factors.The advice that can be given is that Nalu Bowls Restaurant should be able to give agood impression to its customers because by giving a good impression, it can bring thepossibility of the consumer to provide good information to his friends about Nalu Bowls which has an impact on the increasing number of consumers visiting Nalu Bowls.